Communicating Stereotype-Relevant Information: Is Factual Information Subject to the Same Communication Biases as Fictional Information? - Goodman, Ruth L.; Webb, Thomas L.; Stewart, Andrew J. (Personality & social psychology bulletin, 2009)
Factual information is more frequently read and discussed than fictional information. However, research on the role of communication in shaping stereotypes has focused almost exclusively on fictional narratives. In Experiments 1 and 2 a newspaper article containing information about heroin users was communicated along chains of 4 people. No stereotype-consistency bias was observed. Instead, a greater proportion of stereotype-inconsistent information was communicated than was stereotype-consistent or -neutral information. Three further experiments investigated explanations for the difference between the communication of fictional and factual information. Experiment 3 ruled out the possibility that participants' beliefs about the validity of the information could influence the way that it is communicated. Experiments 4 and 5 divided information into concrete (a specific event or fact) or abstract (opinion). A stereotype-consistency bias emerged only for abstract information. In summary, linguistic abstraction moderates whether stereotype-consistency biases emerge in the communication of stereotype-relevant factual information.